Atorvastatin treatment and LDL cholesterol target attainment in patients at very high cardiovascular risk - Laufs, Ulrich (Clin Res Cardiol, 2016)
The use of atorvastatin is rapidly increasing among statins since the introduction of generics. However, only limited data are available on its current use and the effectiveness outside of randomised trials. The aim of the study was to assess low-density lipoprotein (LDL-C) levels in ambulatory patients at very high cardiovascular risk on atorvastatin therapy in physician’s offices. A total of 2625 high-risk patients on atorvastatin were included into this cross-sectional study by 539 office-based physicians between June and December 2014. 47.0 % of the patients had documented coronary heart disease (CHD), 25.1 % type 2 diabetes mellitus (DM), and 27.9 % CHD plus concomitant DM. The mean age was 66.1 ± 10.8 years, 62.1 % were male. Atorvastatin at the dose of 10, 20, 40 and 80 mg/day was administered in 15.6, 45.7, 33.9, and 4.8 % of the patients, respectively. The treatment duration was 92.6 ± 109.6 weeks. The mean atorvastatin dose at therapy start was 24.8 ± 15.2 mg/day and at time of documentation 27.9 ± 15.8 mg/day. Low-density lipoprotein cholesterol (LDL-C) <70 mg/dL was achieved by 10.5 % of the total cohort (7.5 % in DM, 9.3 % in CHD, and 15.2 % in CHD + DM). In contrast, according to physicians’ subjective assessment, 62.7 % of patients (with small differences between groups) had reached their individual LDL-C target. In summary, higher doses of atorvastatin are not frequently used in clinical practice. The LDL-C target level <70 mg/dL as recommended by current guidelines is achieved only in a minority of atorvastatin treated patients at very high cardiovascular risk.